Assessment of heavy metal and trace element levels in patients with telogen effluvium - Ibrahim Halil Yavuz; Goknur Ozaydın Yavuz; Serap Gunes Bilgili; Halit Demir; Canan Demir (Wolters Kluwer Medknow Publications, 2018)
Background: Despite a multitude of studies, etiology of primary chronic telogen effluvium (TE) remains incompletely understood. Essential heavy metals are associated with beneficial effects in humans as well as in other living organisms. However, they may lead to toxic effects when the exposure exceeds the higher tolerable limits. We wanted to assess the heavy metal and trace element levels in patients with chronic TE. Materials and Methods: A total of 40 subjects with chronic TE were included in the study, and 30 healthy women served as control. General and dermatological examinations were taken up in all individuals. Those patients with positive hair pull test were evaluated with the help of a trichogram. The presence of >20% telogen hair as documented by trichogram was a requirement for the study inclusion. UNICAM-929 spectrophotometry device was used for determining serum trace element and heavy metal concentrations. Results: In spite of an absence of significant differences in terms of average Zn concentration, weight, or height between patients and controls, significant differences were noted for Cd, Fe, Mg, Mn, Pb, Co, and Cu (P<0.05). Conclusion: Our results suggest that heavy metals may play a causative role in the development of chronic TE. However, contrary to previous reports, zinc did not appear to play an important etiological role, while these patients had elevated serum iron levels.